A Qualitative Analysis of the Lived Experiences of a Small Group of Filipino Immigrants - Thomas-Brown, Karen; Campos, Annalie L. (Qualitative Sociology Review, 2016)
Demographers have forecasted that the U.S. is rapidly moving closer to becoming a majority-minority country, this fact and the politically divisive nature of recent debates and attempts at immigration reform have fostered increased conversations about citizenship, diversity, assimilation/s, and other im/ migration discourses. Often these dialogues surround boarder-crossings and the political, economic, and social implications of im/migration. One unfortunate outcome is frequently the perpetuation of stereotypes and the “othering” of many migrant groups to which this research offers a counter narrative. This counter narrative is built on the lived citizenship of a small group of Filipino im/migrants in the U.S. The paper demonstrates that—contextually—working abroad is common practice in the Philippines; this phenomenon is woven into the political, social, and economic jurisdictions of the country. This research fills one gap in im/migration studies as it chronicles the stories of these Filipino im/ migrants while examining their perceptions about their identity, sense of belonging, right to place, and the legitimacy of their citizenship socio-culturally. The paper places these and other narratives from this group of im/migrants within the theoretical framework of Critical Theory, hence offering a voice to a group of individuals not frequently heard in academia.